دراسة الخواص المورفولوجية و الفيزيائية و الكيميائية وتطور الترب المتشكلة على صخور كلسية في المنطقة الساحلية (اللّاذقية). - رقية, عادل; غانم, سمر (Tishreen University Journal -Biological Sciences Series, 2018)
For the implementation of this study, profiles of soil formed on calcareous material were selected by the use of geological map of Lattakia 1/50000 scale and the geographical location system GPS. the profiles were prepared and described according to the methods used worldwide in soils morphological study Samples were taken from horizons of each profile and conducted some physical and chemical analysis in addition to the materials of origin. A number of weather indicators were used to estimate the degree of weathering of soil profile. there was a link between rock and limestone on one hand, and between evolution degree of soils profiles and their physical and chemical properties. The chemical analysis and weathering index of soil samples and the parent materials indicated that all soil profiles have been under the weathering agents almost in one degree, with the absence of redistribution of the outputs of the process of weathering. thus there is no significant activity of migration or formation of diagnostic soil, consequence, absence of diagnostic horizons, as a result, the profiles were in the early stages of evolution and recently formed. بهدف تنفيذ هذا البحث تم اختيار قطاعات ترب متشكلة من مادة أصل كلسية بالاستعانة بالخارطة الجيولوجية لمحافظة االلاذقية مقياس 1/50000 وبجهاز تحديد المواقع الجيوغرافية GPS, حضرت المقاطع ووصفت اعتمادا على الطرق المتبعة عالمياً في الدراسة المورفولوجية للتربة. أخذت العينات من آفاق كل مقطع وأجري عليها بعض التحاليل الفيزيائية والكيميائية بالاضافة الى التحليل الكيميائي العام للتربة ولمواد الأصل وتم استخدام عدد من مؤشرات التجوية بهدف تقدير درجة تجوية مادة الاصل وتطور قطاع التربة . كان هناك ارتباط بين الصخر الام الكلسي من جهة وبين تطور القطاعات وخصائصها الفيزيائية والكيميائية. أظهرت نتائج التركيب الكيميائي العام ومؤشرات التجوية, أن جميع آفاق المقاطع المدروسة قد تعرضت لفعل عوامل التجوية بدرجة واحدة تقريباً, مع غياب عملية إعادة توزيع نواتج التجوية, أي لا وجود لنشاط ملحوظ لعملية هجرة آو عملية تكوين تربة تشخيصية وبالتالي لاوجود لآفاق تشخيصية أساسية, وبالنتيجة كانت القطاعات في المراحل الاولى لتطورها و الترب حديثة التكوين و ضعيفة التطور .